Pengaruh Media Pembelajaran Menggunakan Triangle Cardboard Terhadap Hasil Belajar Tendangan Mae Geri - David Sahirul Alim; Hari Wisnu (Simpati, 2024)
Extracurricular karate has many basic techniques, including the mae geri kick technique. The purpose of this study is to improve the skills of karate extracurricular students at SMPN 1 Buduran in the mae geri kick technique. They use triangle cardboard media. This study uses a type of experimental research and a quantitative approach. The research sample consisted of 20 students, 10 students each in the experimental group and 10 students in the control group. Data analysis also uses independent t-tests, normality tests, and data description tests. According to the results of the hypothesis test on the results of the influence of learning media using triangle cardboard on the learning outcomes of mae geri kicks of extracurricular students of SMPN 1 Buduran Sidoarjo has a sig value of 0.00 < 0.05, so that it can be stated that there is an influence of learning media using triangle cardboard on the learning outcomes of mae geri kicks in extracurricular students of SMPN 1 Buduran Sidoarjo. According to calculations made using the SPSS version 25 computer program, the above statement is the conclusion that the experimental group has a greater improvement than the control group. The results of the calculation showed a 158% increase in learning media using triangle cardboard on the learning outcomes of mae geri kicks, while an increase of 60% in the control group